Pengaruh Profitabilitas, Likuiditas, dan Leverage terhadap Nilai Perusahaan: Studi pada Perusahaan Sektor Kesehatan yang Terdaftar di BEI Tahun 2022-2024 - Nur Jauharin Insi’ah; Riska Ayu Setiawati (Jurnal Manajemen Bisnis Era Digital, 2026)
This study aims to analyze the influence of profitability, liquidity, and leverage on firm value, both partially and simultaneously. The background of this study is based on the importance of firm value as an indicator of managerial performance and a factor that attracts investor attention. The approach used is quantitative with a causal-associative research type. The data used is secondary data obtained from the financial statements of 19 companies in the healthcare sector. Based on the analysis, the results indicate that profitability has a positive and significant effect on firm value, indicating that good financial performance can increase market perception of firm value. On the other hand, liquidity and leverage do not show a significant effect on firm value. This indicates that these two factors do not significantly influence market assessments of companies in the healthcare sector that are the object of this study. However, simultaneously, all three variables are proven to have a significant effect on firm value, indicating that although their partial effects are different, all three factors have a collective contribution in shaping firm value. From the results of this study, it can be concluded that profitability is the main factor that plays a role in increasing firm value, while liquidity and leverage require further attention in a more specific context.